2022
DOI: 10.1021/acsphotonics.1c01935
|View full text |Cite
|
Sign up to set email alerts
|

Submicron Organic–Inorganic Hybrid Radiative Cooling Coatings for Stable, Ultrathin, and Lightweight Solar Cells

Abstract: Solar cell technology requires materials that are efficient, lightweight, and stable. Organic–inorganic lead halide perovskite- and polymer-based bulk heterojunction solar cells have emerged as highly promising, ultralightweight, flexible, and highly efficient power sources. However, they suffer from limited stability, which is significantly affected by the cell temperature, in addition to other factors like oxidization and moisture in the absence of appropriate encapsulation. Here, by performing a coupled opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…According to Stefan-Boltzmann law, the infrared emission peak of photovoltaic panels (≈60 °C) is within the atmospheric window of 8-13 μm, which is the basic principle for radiative pho-tovoltaic cooling. [54,101,[129][130][131][132][133][134] In 2014, Fan's group re-proposed the promising passive cooling method of photovoltaic panels via radiative cooling. [135] They developed the modeling for photovoltaic panels with radiative coolers and revealed that the cooling method can enable a great temperature drop of ≈18.3 K, compared to that of the bare silicon absorber.…”
Section: Radiative Coolingmentioning
confidence: 99%
“…According to Stefan-Boltzmann law, the infrared emission peak of photovoltaic panels (≈60 °C) is within the atmospheric window of 8-13 μm, which is the basic principle for radiative pho-tovoltaic cooling. [54,101,[129][130][131][132][133][134] In 2014, Fan's group re-proposed the promising passive cooling method of photovoltaic panels via radiative cooling. [135] They developed the modeling for photovoltaic panels with radiative coolers and revealed that the cooling method can enable a great temperature drop of ≈18.3 K, compared to that of the bare silicon absorber.…”
Section: Radiative Coolingmentioning
confidence: 99%
“…Besides, small thickness of the designed absorber is one of advantages. Thus, the proposed meta-surface as a coating of solar cells is a direction worth considering [35,36].…”
Section: Structural Design Of Absorber With Wide Spectrum and High Ab...mentioning
confidence: 99%
“…31,32 Organic-based materials are ubiquitous in our daily life thanks to their scalability, versatility, and easy manufacturing. Nowadays, more and more organic-based radiative cooling materials are processed to include air voids to promote ultrabroadband sunlight reflection and effective thermal-infrared emission, 33 such as nano-porous membranes, 34,35 nanofiber membranes, 36,37 organic-inorganic composite membranes, [38][39][40] and nano-porous gel with high reflectivity. 41,42 The main advantages of organic-based radiative cooling materials are their scalability, mechanical resistance and flexibility, weather resistance, and electric insulation, making them suitable for outdoor applications.…”
Section: Introductionmentioning
confidence: 99%